2021
DOI: 10.1002/pon.5770
|View full text |Cite
|
Sign up to set email alerts
|

Psychological resilience of patients with bladder cancer after radical cystectomy and urinary diversion: A cross‐sectional study

Abstract: Objective:The aims of this study were to investigate the current state of psychological resilience and identify its associated factors in bladder cancer (BC) patients undergoing radical cystectomy (RC). Methods:A cross-sectional study, using convenience sampling was conducted among 248 patients recruited from urology department of a tertiary hospital in Shenyang, China. According to the resilience in illness model, participants were invited to finish a questionnaire included demographic and disease-related inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…As a protective factor for individuals to cope with stress, psychological resilience can change with the surrounding pressure and then play a positive role in regulating psychology and adapting to stress. Psychological resilience was found to be better for physical and mental health preparations in HCWs who were more adapted to the work (Dong et al, 2022 ; Finstad et al, 2021 ). Thus, the demand for physical and mental health preparations was higher (Dong et al, 2022 ; Finstad et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a protective factor for individuals to cope with stress, psychological resilience can change with the surrounding pressure and then play a positive role in regulating psychology and adapting to stress. Psychological resilience was found to be better for physical and mental health preparations in HCWs who were more adapted to the work (Dong et al, 2022 ; Finstad et al, 2021 ). Thus, the demand for physical and mental health preparations was higher (Dong et al, 2022 ; Finstad et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Psychological resilience was found to be better for physical and mental health preparations in HCWs who were more adapted to the work (Dong et al, 2022 ; Finstad et al, 2021 ). Thus, the demand for physical and mental health preparations was higher (Dong et al, 2022 ; Finstad et al, 2021 ). Therefore, hospital management personnel can establish precise training and intervention measures based on the influencing factors of job demands in mobile cabin hospitals to improve HCWs' emergency response ability and advance their career growth to achieve the purpose of normalized emergency prevention and control management.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis found that the coping mode can be roughly divided into two categories; that is, some coping styles have more positive components, such as seeking support and trying to change, and some are mainly negative elements, such as avoidance and venting (Frantsve et al, 2008; Parker et al, 1986; Santarnecchi et al, 2018). Previous studies reported that positive coping strategies have a positive effect on resilience in cancer patients (Dong et al, 2021; Lai et al, 2020; Macía et al, 2020; Wu et al, 2021).…”
Section: Introductionmentioning
confidence: 98%